Computation of aeroacoustic sources for a Gulfstream G550 nose landing gear model using adaptive FEM. (2nd January 2016) - Vilela de Abreu, Rodrigo; Jansson, Niclas; Hoffman, Johan
Highlights: We present a "parameter-free" methodology for computational aeroacoustics (CAA). We use a FEM with adaptive mesh generation based on a posteriori error estimates. We carefully compare our simulation with available experimental data. Abstract: This work presents a direct comparison of unsteady, turbulent flow simulations with measurements performed using a Gulfstream G550 nose landing gear model. The experimental campaign, which was carried out by researchers from the NASA Langley Research Center, provided a series of detailed, well documented wind-tunnel measurements for comparison and validation of computational fluid dynamics (CFD) and computational aeroacoustics (CAA) methodologies. Several computational efforts were collected and presented at the Benchmark for Airframe Noise Computation workshops, BANC-I and II. For our simulations, we used a General Galerkin finite element method (G2), where no explicit subgrid model is used, and where the computational mesh is adaptively refined with respect to a posteriori estimates of the error in a quantity of interest, here the source term in Lighthill's equation. The mesh is fully unstructured and the solution is time-resolved, which are key ingredients for solving problems of industrial relevance in the field of aeroacoustics. Moreover, we choose to model the boundary layers on the landing gear geometry with a free-slip condition for the velocity, which we previously observed to produce good results for external flows at high Reynolds numbers, and which considerably reduces the amount of cells required in the mesh. The comparisons presented here are an attempt to quantify the accuracy of our models, methods and assumptions; to that end, several results containing both time-averaged and unsteady flow quantities, always side by side with corresponding experimental values, are reported. The main finding is that we are able to simulate a complex, unsteady flow problem using a parameter-free methodology developed for high Reynolds numbers, external aerodynamics and aeroacoustics applications.